The role of the French philosopher Gaston Bachelard in the development of epistemological thinking - رزوق , ابراهيم; بشو, محمد مصطفى (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The French philosopher of contemporary science, Gaston Bachelard, has clearly and accurately expressed the nature of the dialectical relationship between science and method by saying: When science changes its methods, it becomes more systematic. And a method of analyzing scientific knowledge. For this reason, we see Bachelard and in most of his works confirm that the main tasks of epistemology are to carry out a psychological analysis of objective knowledge Bachelard has tried hard to clarify the basic picture that links epistemology to psychoanalysis, by searching for basic concepts such as the concept of epistemological obstacle and the concept of epistemological rupture and epistemological obstacle, from which epistemological analysis benefits from psychoanalysis and which helps him analyze scientific knowledge. } which was advocated by Sigmund Freud, which is based mainly on the suppression of desires that cannot be fulfilled in reality and is called (psychological repression), whereby Bachelard was able, through the psychoanalytic approach of scientific knowledge, to transfer the field of its application from the personal psychological life of humanity to the field of scientific and cognitive work. Epistemological obstacles are the manifestation of the disruption, cessation, or regression of scientific workAnd it is basically the result of the process of this scientific work itself, in a more precise sense that there can be no scientific work without there being obstacles or epistemological obstacles. The history of science, as Bachelard sees, is a debate between the obstacles and epistemological breaks.